Phase I study of the checkpoint kinase 1 inhibitor GDC-0575 in combination with gemcitabine in patients with refractory solid tumors. (23rd February 2018) - Italiano, A; Infante, J R; Shapiro, G I; Moore, K N; LoRusso, P M; Hamilton, E; Cousin, S; Toulmonde, M; Postel-Vinay, S; Tolaney, S; Blackwood, E M; Mahrus, S; et al.
Abstract: Background: Checkpoint kinase 1 (Chk1) inhibition following chemotherapy-elicited DNA damage overrides cell cycle arrest and induces mitotic catastrophe and cell death. GDC-0575 is a highly-selective oral small-molecule Chk1 inhibitor that results in tumor shrinkage and growth delay in xenograft models. We evaluated the safety, tolerability, and pharmacokinetic properties of GDC-0575 alone and in combination with gemcitabine. Antitumor activity and Chk1 pathway modulation were assessed. Patients and methods: In this phase I open-label study, in the dose escalation stage, patients were enrolled in a GDC-0575 monotherapy Arm (1) or GDC-0575 combination with gemcitabine Arm (2) to determine the maximum tolerated dose. Patients in arm 2 received either i.v. gemcitabine 1000 mg/m 2 (arm 2a) or 500 mg/m 2 (arm 2b), followed by GDC-0575 (45 or 80 mg, respectively, as RP2D). Stage II enrolled disease-specific cohorts. Results: Of 102 patients treated, 70% were female, the median age was 59 years (range 27–85), and 47% were Eastern Cooperative Oncology Group PS 0. The most common tumor type was breast (37%). The most frequent adverse events (all grades) related to GDC-0575 and/or gemcitabine were neutropenia (68%), anemia (48%), nausea (43%), fatigue (42%), and thrombocytopenia (35%). Maximum concentrations of GDC-0575 were achieved within 2 hours of dosing, and half-life was ∼23 hours. No pharmacokinetic drug–drug interaction was observed between GDC-0575 and gemcitabine. Among patients treated with GDC-0575 and gemcitabine, there were four confirmed partial responses, three occurring in patients with tumors harboring TP53 mutation. Pharmacodynamic data were consistent with GDC-0575 inhibition of gemcitabine-induced expression of pCDK1/2. Conclusion: GDC-0575 can be safely administered as a monotherapy and in combination with gemcitabine; however, overall tolerability with gemcitabine was modest. Hematological toxicities were frequent but manageable. Preliminary antitumor activity was observed but limited to a small number of patients with a variety of refractory solid tumors treated with GDC-0575 and gemcitabine. Clinical trial number: NCT01564251.